Inhibition of Peripheral Synthesis of Serotonin as a New Target in Neuroendocrine Tumors - Molina-Cerrillo, Javier (Oncologist, 2016)
The carcinoid syndrome represents a set of signs and symptoms associated with neuroendocrine tumors (NETs) that occur primarily when metastases are developed in the liver, resulting in the worsening of quality of life. Serotonin plays a central role in the physiology of carcinoid syndrome by promoting intestinal motility. Somatostatin analogs (SSAs) have widely demonstrated their efficacy as symptomatic relievers of carcinoid syndrome, but this control is ephemeral, being reduced by approximately 50% within the first year. The exact mechanisms of resistance to SSAs are not fully understood, but it is believed that serotonin might be involved. Patients with carcinoid syndrome present with a significant increase in serotonin plasma levels and, consequently, in the soluble urinary metabolite 5-hydroxyindole acetic acid. Telotristat etiprate is a potent inhibitor of tryptophan hydroxylase, a rate-limiting enzyme in the synthesis of serotonin, that has demonstrated in the phase III TELESTAR clinical trial a significant improvement in the control of bowel movements in patients with NETs who have carcinoid syndrome and who have progressed to an SSA. Based on these results, telotristat etiprate has emerged as a potential new option in the treatment algorithm of symptomatic control of functioning NETs. However, some issues need to be clarified, such as the safety profile of the drug outside clinical trials, the benefit in quality of life, and the possible impact on tumor growth, as well as its role within sequencing or combination treatment strategies with pre-existing drugs effective in NET treatment. IMPLICATIONS FOR PRACTICE: This article reviews the literature about carcinoid syndrome, which affects patients diagnosed with neuroendocrine tumors. Few articles have been published about this syndrome and its pathophysiology. Somatostatin analogs provide symptomatic relief; however, patients may become refractory to this strategy, usually within the first year of treatment. In this context, as an agent with an innovative mechanism of action, telotristat etiprate has demonstrated activity in a phase III trial, and findings may offer a path to an improve quality of life and prolonged survival for certain patients.